Adventitious roots and lateral roots: similarities and differences - Bellini, Catherine; Pacurar, Daniel I; Perrone, Irene (Annual review of plant biology, 2014)
In addition to its role in water and nutrient uptake, the root system is fundamentally important because it anchors a plant to its substrate. Although a wide variety of root systems exist across different species, all plants have a primary root (derived from an embryonic radicle) and different types of lateral roots. Adventitious roots, by comparison, display the same functions as lateral roots but develop from aerial tissues. In addition, they not only develop as an adaptive response to various stresses, such as wounding or flooding, but also are a key limiting component of vegetative propagation. Lateral and adventitious roots share key elements of the genetic and hormonal regulatory networks but are subject to different regulatory mechanisms. In this review, we discuss the developmental processes that give rise to lateral and adventitious roots and highlight knowledge acquired over the past few years about the mechanisms that regulate adventitious root formation.